2022
DOI: 10.21203/rs.3.rs-2201470/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Hidden blood loss and its possible risk factors in full endoscopic lumbar interbody fusion

Abstract: Objective Full endoscopic lumbar interbody fusion (ELIF) is a representative recent emerging minimally invasive operation, and its effectiveness has been continuously proved. This study aimed to evaluate the hidden blood loss in ELIF procedure and its possible risk factors. Methods The blood loss was calculated by Gross formula. Sex, age, BMI, hypertension, diabetes, ASA classification, fusion levels, surgical approach type(the count of trans-Kambin approach and interlaminar approach), surgery time, preopera… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 25 publications
1
0
0
Order By: Relevance
“…Therefore, tumor volume and the length and site of operation were used to substitute for operation time, and reflect the individual feature. The results indicated that the increase in length of operation associated with more HBL, which was in accordance with the research of Ge et al 32 Additionally, it was found that operation sites was a significant indicator for HBL. This may be related that paraspinal soft tissue thickness varies across the vertebral column, and studies have suggested an association of soft tissue thickness with greater soft tissue injury and larger tissue space for potential infiltration of blood 33,34 .…”
Section: Discussionsupporting
confidence: 91%
“…Therefore, tumor volume and the length and site of operation were used to substitute for operation time, and reflect the individual feature. The results indicated that the increase in length of operation associated with more HBL, which was in accordance with the research of Ge et al 32 Additionally, it was found that operation sites was a significant indicator for HBL. This may be related that paraspinal soft tissue thickness varies across the vertebral column, and studies have suggested an association of soft tissue thickness with greater soft tissue injury and larger tissue space for potential infiltration of blood 33,34 .…”
Section: Discussionsupporting
confidence: 91%